2014
DOI: 10.1111/ejn.12475
|View full text |Cite|
|
Sign up to set email alerts
|

No more pain upon Gq‐protein‐coupled receptor activation: role of endocannabinoids

Abstract: Marijuana has been used to relieve pain for centuries. The analgesic mechanism of its constituents, the cannabinoids, was only revealed after the discovery of cannabinoid receptors (CB1 and CB2) two decades ago. The subsequent identification of the endocannabinoids, anandamide and 2-arachidonoylglycerol (2-AG), and their biosynthetic and degradation enzymes discloses the therapeutic potential of compounds targeting the endocannabinoid system for pain control. Inhibitors of the anandamide and 2-AG degradation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 246 publications
(351 reference statements)
0
11
0
1
Order By: Relevance
“…With respect to acute stress, there is evidence that an increase in eCB signaling contributes to non-opioid stress-induced analgesia (Hu et al, 2014). The initial demonstration of this effect found that CB1 receptor-deficient mice did not exhibit antinociception following exposure to swim stress (Valverde et al, 2000).…”
Section: Functional Role Of Ecb Signaling In the Neurobiological Effementioning
confidence: 99%
“…With respect to acute stress, there is evidence that an increase in eCB signaling contributes to non-opioid stress-induced analgesia (Hu et al, 2014). The initial demonstration of this effect found that CB1 receptor-deficient mice did not exhibit antinociception following exposure to swim stress (Valverde et al, 2000).…”
Section: Functional Role Of Ecb Signaling In the Neurobiological Effementioning
confidence: 99%
“…In this context, it is interesting that patients with PTSD -in contrast to patients with PD and phobia -display no reduction of inhibitory 5-HT 1 R binding sites in any of the assessed neocortical and subcortical regions including PFC, FC, PC, TC, OC, CING, HIPP, AMYG, INS, PHG and MB (Bonne et al, 2005;Sullivan et al, 2009). Since PTSD per definition involves the singular or repeated infliction of an extrinsic (physical) trauma, 5-HT (and, for that matter, also DA and GABA) function may be basically altered in this subtype by interaction with neurotransmitters relevant for the mediation of nociception and acute and/or chronic stress such as substance P (for review, see Nikolaus et al, 2013), noradrenaline (for review, see Yamamoto et al, 2014), endocannabinoids (for review, see Hu et al, 2014) and endogenous opiates (for review, see Spetea, 2013).…”
Section: Appraisal Of Resultsmentioning
confidence: 99%
“…We start by dissecting pathogenic mechanisms underscoring nociceptive and neuropathic mechanisms of chronic pain, with specific emphasis on skeletal pain (Mantyh, ) and osteoarthritis pain (that is, associated with degenerative joint disease; La Porta et al ., ), and by discussing the role of major genetic variations (Capsoni, ; Di Lorenzo et al ., ; Indo, ). Next, contributions are aimed at disentangling novel nodes of pain‐related signalling in neurons; in particular, they address with outstanding precision and attention to novel facets of information the specific contributions of both endocannabinoids and neurotrophins, more specifically nerve growth factor (NGF) and its receptors, at successive levels of hierarchically organized pain pathways (Horváth et al ., ; Hu et al ., ; Keimpema et al ., ).…”
mentioning
confidence: 97%
“…In the adult, molecular components of endocannabinoid metabolism, as well as CB 1 R and TRPV1, are expressed at many levels in neuronal pathways (dorsal root ganglia, spinal dorsal horn, periaqueductal gray, hippocampus, neocortex) transducing nociceptive information (Hohmann & Suplita, ; Horváth et al ., ; Hu et al ., ). Exogenous administration of endocannabinoids (2‐arachidonoylglycerol is shown here; Rea et al ., ) and phytocannabinoids (Hu et al ., ) suppress noxious stimulus‐evoked neuronal activity in nociceptive neurons in the spinal cord, periaqueductal gray, thalamus and hippocampus in a cannabinoid receptor‐dependent fashion (for review see Hohmann & Suplita, ). Moreover, ‘on‐demand’ endocannabinoid production is driven by G protein‐coupled receptor (GPCR) signalling through Gq inducing a phospholipase C‐ sn ‐1‐diacylglycerol lipase cascade (Hu et al ., ).…”
mentioning
confidence: 99%
See 1 more Smart Citation